Impacto de diferentes metodos de ensino no desempenho tatico-tecnico no badminton - Layla Maria Campos Aburachid (2015)
This study was based to promote the sport pedagogy area searching for academicscientific support to proceeding to teaching and learning. It ain was to analyze the impact of three teaching methods in tactical and technical performance of badminton beginners. The research was developed in three phases, each of which corresponds to the proposed specific objectives so defined: in phase one, three teaching methodswere characterized after 17 sessions of lessons from the systematic observation of the structural and tasks complexity of activities. The badminton beginners in a total of 64 subjects (15.1 } 0.64) were divided into four groups of 16 participants who received intervention using different teaching methods, besides the subdivision stratified by sex: technical teaching method (GE1), tactical teaching method (GE2),integrative teaching method (GE3) and control group (CG). In phase two, where determined the impact of teaching methods at the tactical and technical performance of the subjects, considering time and sex, through the application of four tests. In step three, the practice motivation level was evaluated during the implementation of interventions, taking into account the teaching methods and the evaluation times. The results of categorization confirmed the teaching methods employed to experimental groups. The method focuses on technique presented for tactical variables small impact results for declarative tactical knowledge (2 partial 0, 184) and game performance (2 partial 0, 239) only for boys. For technical variables the results were similar to the skill execution index (2 partial 0,241), without significant differences in the motivation level. The methods focused on tactical presented for tactical variables a large impact in the decision making index for boys (integrative teaching method 2 partial 0,386 and tactical teaching method 2 partial 0,426) andmiddle impact for girls only at the tactical teaching method (2 partial 0,274). For both tactical methods (integrative e tactical teaching methods) game performance had small impact (2 partial 0,165; 0,220) only for girls. Regarding technical variables the boys from integrative teaching method presented small impact on the service evolution (2 partial 0,212). Concerns to boy`s clear, where found middle impact supported by intervention for the tactical teaching methods (2 partial 0,355) and big impact for the integrative teaching methods (2 partial 0,398) intervention. The general extrinsic motivation level achieved small impact for boys at the integrative method (2 partial 0,241). The influence of the intrinsic and extrinsic motivation level of participants in the integrative teaching method on the technical and tactical evolution effects explained 55% of variance (p=0.001) and 40% of variance (p=0.008), respectively. In conclusion, for girls the most recommended teaching method is the tactical and for boys integrative teaching method. The learning gains in the integrative teaching method were superior in number of variables affected bothtactics and techniques as with middle to high impacts.